Concomitant atopic dermatitis and psoriasis – a retrospective review. (3rd October 2021) - Barry, Kelly; Zancanaro, Pedro; Casseres, Rachel; Abdat, Rana; Dumont, Nicole; Rosmarin, David
Abstract: Introduction: At one time considered opposing diseases, it is now recognized that atopic dermatitis (AD) and psoriasis can coexist. There are limited data characterizing this population of patients. In this study, we characterize the population of patients diagnosed with both AD and psoriasis and summarize their response to therapy. Methods: A retrospective chart review was performed and data was recorded for patients with a diagnosis of psoriasis ( n  = 1390), AD ( n  = 912) and psoriasis plus AD ( n  = 30) within the Tufts Medical Center Department of Dermatology between January 1, 2012 and May 1, 2019. Results: The prevalence of concomitant AD and psoriasis was 1.5%. Of those with both AD and psoriasis, hand involvement was high (63%). Systemic therapy was used in 73% of patients. Of those on biologics, 30% required more than one biologic consecutively and 22% required more than one biologic simultaneously to achieve clinically significant results. Conclusion: Patients with overlapping AD and psoriasis have a high prevalence of hand involvement, poor response to topical therapy, and may require multiple systemic agents to treat. In a patient with known history of psoriasis with recalcitrant hand disease involvement, AD should be considered.